KEIKUTSERTAAN INDONESIA DI WORLD HEALTH ASSEMBLY (WHA) DALAM MENANGANI VIRUS FLU BURUNG H5N1 - Safitri, Elsa; Fachri, Yuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes Indonesia in dealing with the problem of avian influenza virus H5N1 that’s where the pandemic of this virus spread further from year to year. Indonesia makes policies towards getting new nutbreak of the avian influenza H5N1 virus by making vaccine samples of H5N1 virus, which afterwards the samples are sent to World Health Organizations (WHO). Associated with the vaccine, there is statement : How Indonesia participation in the World Health Assembly (WHA) in addressing the problem of avian influenza H5N1 virus”.On the December 20, 2006 the government of Indonesia ( Ministry of Health ) issued a policy to stop the shipments of the virus to WHO because of cheating conducted by World Health Organizations (WHO) and Australia in the use of vaccines and sell vaccines with very expensive price.Indonesia share avian influenza vaccine utilization in order to be used by developing countries at affordable prices in accordance with the resolution of World Health Assembly (WHA) concerning PIP ( Pandemic Influenza Preapradness ), Framework : sharing influenza Viruses and Access to Vaccines and other benefits, and the PIP Framework is in line with the Nagoya Protocol on genetic resources and this genetic resourcesis in protect by patents, namely Act No. 14 of 2001.Keywords: Avian Influenza Virus H5N1, Vaccine, WHA, Patents, The Nagoya Protocol